Digital afterlife: (eco)civilizational politics of the site and the sight of e-waste in China - Zuev, D. (Anthropology Today, 2018)
This article aims to examine the ongoing changes in ‘green politics’ in China by focusing on the example of e-waste recycling and, specifically, transformations in one given town, Guiyu. It is argued that the spontaneous stage of development in e-waste recycling in Guiyu has become the object of civilizational politics, which includes the formalization, centralization and spatial and visual evolution of the recycling site. Civilizational politics is conceptualized as an approach towards adapting to the existing socio-technical conditions and the introduction of a new infrastructural regime, which is discursively framed as a civilized one: modern, environmentally friendly and socially beneficial. The ‘informal’ sector in e-waste recycling is the main target of civilizational politics, as it is associated with ‘low-tech’ and polluting technologies and small-scale enterprises powered by migrant labour. While the target of civilizational politics is upscaling via the creation of large, centralized, ‘formal’ facilities, the social and environmental sustainability of such a transition should be questioned.